Facile High-Yield Growth of One-Dimensional van der Waals Ta2Pd3Se8 via Chemical Vapor Transport Using PdCl2 as a Transport Agent - Zhang, Xiaojie; Kang, Jinsu; Choi, Kyung Hwan; Jeon, Jiho; Jeong, Byung Joo; Bang, Hyeon Seok; Oh, Hyung Suk; Lim, Jongwoo; Park, Jae Hyuk; Lee, Jae Hyun; Yu, Hak Ki; Choi, Jae Young (Chemistry of Materials, 2024)
Chemical vapor transport (CVT) is a commonly used method for growing single crystals. Halogens and their compounds are widely employed as transport agents owing to their low sublimation points. To increase the yield of produce, this study explored the species type and amount of transport agents as well as the synthesis temperature and time to achieve the maximum optimization of the synthesis process of Ta2Pd3Se8 nanowires. Four transport agents, namely, PdCl2, PdBr2, I2, and Se, were thermodynamically analyzed and compared, and PdCl2 was deemed the most suitable agent for Ta2Pd3Se8 field-effect transistor applications. The high current on/off ratio of approximately 105 and mobility of 13.8 cm2 V-1 s-1 obtained for the Ta2Pd3Se8 nanowires via the improved CVT method were further confirmed by analyzing their electrical properties. Additionally, a method for selecting the optimal transport agent, amount of transport agent, and temperature and time of the CVT reaction is presented for growing single crystals with maximum yields.
Keywords: Chemical Vapour Transport; Higher yield; Maximum optimisation; One-dimensional; Synthesis process; Synthesis temperatures; Synthesis time; Transport agent; Van der Waal; Yield growth